The association between procrastination and negative emotions in healthy individuals: a systematic review and meta-analysis - Nie, Yuyang; Wang, Wenlei; Zhou, Fangbing; Wang, Tianci; Li, Simin; Liu, Cong; Gao, Jinchao (Frontiers in Psychiatry, 2025)
IntroductionThe widespread recognition of the link between procrastination and negative emotions is accompanied by a need for greater clarity regarding the underlying mechanisms of this connection. This study aims to systematically review and meta-analyze the association between procrastination and negative emotions, specifically focusing on depression, anxiety, and stress.MethodsThrough comprehensive searches across five databases, we have included a total of 88 studies, encompassing 63,323 participants across 17 countries. Utilizing Stata 18.0, we conducted separate meta-analyses for each of the three negative emotions.ResultsThe results indicate a moderate positive correlation between procrastination and negative emotions, with a combined effect size of r=0.342. Subgroup analyses reveal variations in the strength of this association across different types of procrastination. Furthermore, the results of the publication bias test indicate no significant bias.DiscussionBy unveiling the close connection between procrastination and negative emotions, and preliminarily exploring the bidirectional relationship between procrastination and negative emotions based on the included longitudinal studies, this study has reinforced the theoretical foundation of this field. Policymakers should consider the association with procrastination behaviors when aiming to improve people’s mental health and well-being.Systematic Review Registration: PROSPERO (CRD420251041427).